The ANALYSIS OF AN ACADEMIC FRAUD BEHAVIOR BASED ON THE FRAUD HEXAGON THEORY - Sutarto, Herkulanus Sugiono; Putra, I Gusti Bagus Agung Hendrawan; Susandya, Anak Agung Putu Gede Bagus Arie (Indonesia Auditing Research Journal, 2024)
The purpose of this study is to obtain empirical evidence of the influence of pressure, opportunity, rationalization, capability, arrogance, and collusion on academic fraud behavior Students of the Bachelor of Accounting Study Program Faculty of Economics and Business, Universitas Mahasaraswati Denpasar. The population in this study is students of the Bachelor of Accounting Study Program with a population of 494 students. The number of samples in this study was 221 respondents. Researchers used the Proportionate Stratified Random Sampling technique. This study used the Slovin formula to determine the number of samples to be used. The data analysis technique used in this study is multiple linear regression analysis. The result of this study is that rationalization, capability, and arrogance positively affect academic fraud behavior, while pressure, opportunity, and collusion do not affect academic fraud behavior.